THE ROLE OF CALCITONIN IN THE PREOPERATIVE STAGE AS THE PREDICTOR OF MEDULLARY THYROID CANCER METASTASES - Palamarchuk , Volodymyr; Smolyar , Viktor; Tovkay , Oleksandr; Nechay , Oleksandr; Kuts , Volodymyr; Sichinava , Revaz; Mazur , Oleh (The Ukrainian Scientific Medical Youth Journal, 2021)
the aim of the stydy was to analyze the detectability of medullary thyroid metastases in patients at treatment and diagnostic stages, to investigate the applicability of serum calcitonin level as predictor of possible presence of medullary thyroid metastases. The study included data from 148 patients who underwent surgical treatment for the initial diagnosis of medullary thyroid cancer. The age of patients ranged from 12 to 83 years, the mean age was 48,2±1,9 years; the distribution by gender was as follows: men – 34 (23%), women – 114 (77%). Patients were divided into two groups depending on the pathomorphological report: 1 group (100 (67,6%) – patients without metastases), 2 group (48 (32,4%) – patients with locoregional metastases). Among 148 studied patients with medullary thyroid cancer, as a result of the histopathological conclusion, in 48 (32,4%) metastases were detected in regional lymph nodes, among which 10 (6,7%) patients had metastases only in the central collector and 38 (25, 7%) –both in the central and lateral collectors. At the preoperative stage, the level of undiagnosed metastases by ultrasound was 64,58% (31 patients). Subsequently, at the intraoperative stage, during the rapid histological biopsy, the number of undiagnosed metastases decreased to 37,5% (18 patients), and in the postoperative period, according to the results of histopathological examination, the remaining patients were diagnosed with the medullary thyroid cancer metastases. Ultrasound helped to detect metastases in 17 patients, which was 35,42% of all detected metastases. At the stage of intraoperative study, the detection of metastases increased and amounted to 30 (62,5%), and in the postoperative period as a result of histopathological examination metastases were confirmed in 48 patients (100%). Quantitative indicators of both detected and undiagnosed metastases at all stages of treatment and diagnostic search are statistically significant (p<0,01). The detection of metastases in the central lymphatic collector (N1a) at the preoperative stage was 2,08%, this index has doubled (to 4,16%) after intraoperative rapid histological conclusion, and after histopathological conclusion the index has increased more than 10 times (20,84 %). This tendency to grow of metastaseses detection was followed also on lateral collectors: N1b and psilateral were observed at 15 (31,2%) patients at the preoperative stage, their number increased to 23 (47,9%) intraoperatively and to 31 (64,6%) postoperatively; N1b contralateral was observed in 1 (2,1%), 5 (10,4%) and 7 (14,6%), respectively. Such a low percentage of metastases detection at the preoperative stage by ultrasound prompted to CT level study as the predictor of possible metastases. We investigated the preoperative basal blood CT value as a marker of the medullary thyroid cancer metastases presence probability. Due to the small number of the group (n=10) with N1a, the association of CT (cut-off level 137 pg/ml) with the possible presence of metastases was not significant (AUC = 0.594), while in the group with N1b there was a more significant difference. Thus, CT cut-off levels of 358 pg/ml for N1b ipsilateral, and 498 pg/ml for N1b contralateral detection of possible metastases in collectors, with AUC: 0.877 and 0.832, respectively, which justifies the importance of the lateral neck dissection in addition to the mandatory central dissection in order to remov possible medullary thyroid cancer metastases. Thus, ultrasound is insufficiently reliable method of metastases verifying in medullary thyroid cancer (DE = 35.4% at d mts <0.6 cm). In the absence of ultrasound data (or fine needle aspiration (FNA) biopsy results) on the presence of metastases to raise awareness of the disease prevalence, to clarify the prognosis of its development it’s important to use the additional criterion – the calcitonin level. Basal calcitonin level is the reliable predictor of the medullary thyroid cancer metastases. Its cut-off level of 137 pg/ml indicates the possible presence of metastases in the central group (N1a) (AUC=0,594). The CT cut-off level – 358 pg/ml (AUC=0,793) suggests the presence of the medullary thyroid cancer metastases (N1a+N1b). CT cut-off levels – 358 pg/ml for N1b ipsilateral, and 498 pg / ml for N1b contralateral (AUC: 0,877 and 0,832), respectively. The calculated values of the countersensitivity test to detect metastases for different levels of basal CT in the preoperative stage in the clinical setting will help the practitioner in deciding on treatment tactics to determine the extent of surgery in patients diagnosed (or suspected) with the medullary thyroid cancer metastases.